The Association between Leptin and Asprosin Levels in Female Patients with Type II Diabetes Mellitus - Bakr, Duha Q.; Abed , Ahmed Y. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Leptin and asprosin are adipokines secreted by white adipose tissue. The leptin and asprosin molecules have many functions in the central nervous system and other functions of the body: Appetite, glucose ‎metabolism, ‎insulin resistance, and cellular death.Objectives: The study aims to determine the potential relationship between leptin and asprosin hormones in female patients with type II diabetes mellitus.Methods: The present study was conducted in Al-Mahmodia Hospital / Baghdad and the laboratories of the College of Science for Girls / University of Baghdad / Iraq, for the period from 1/11/2023 to 1/2/ 2024. This study is a comparative analysis of several essential biomarkers ‎found in the sera of individuals with diabetes via estimating leptin, asprosin, fasting blood glucose, glycated ‎hemoglobin, body mass index, total cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase in females with type II diabetes mellitus. The study consisted of 60 participants grouped into: Group I (30 females ‎with diabetes), and group II (30 healthy females). The Biochemical ‎parameters of every participant were ascertained. The quantification of leptin and asprosin in the serum was conducted using the enzyme-linked immunosorbent assay (ELISA).Results: The levels of leptin and asprosin were markedly high in the diabetic group [(‎5.1 ± 0.69‎‎), and (10.3 ± 1.07)] compared with the control group [(2.0 ± 0.48), and (1.6 ± 0.16)] respectively, with a significant difference. Conclusion: Despite the high levels of leptin and asprosin in female patients with Type II diabetes mellitus, the relationship between leptin and asprosin was a weak negative one.